TEACHING AND LEARNING HISTORY THROUGH GAMES AND PLAYFULNESS IN BASIC EDUCATION FOR YOUNG PEOPLE, ADULTS, AND THE ELDERLY - Soares, Kauan Pessanha; Pedrosa, Stella Maria Peixoto de Azevedo (Seven Editora, 2025)
This work discusses the use of digital games as pedagogical resources in the teaching of History in Basic Education, focusing on the Education of Young People, Adults, and the Elderly. It starts from the understanding that digital culture and technological artifacts reconfigure social and educational practices, demanding methodological approaches that integrate analog and digital mediations. Based on a literature review, the role of play in historical learning is analyzed, as well as the relationships between representation, narrative, and meaning-making in digital games considered history games. Grounded in authors such as Rüsen, White, Huizinga, Pereira, and Gee, the study identifies that digital games enhance the development of historical awareness, imagination, and historical reasoning by allowing immersion, simulation, and contextualized decision-making. The results indicate that, although originally conceived for entertainment, games can constitute learning devices when critically mediated by the teacher, articulated with the curriculum, and used for comparative analysis with historiographical sources. It is concluded that its use does not replace other methodologies, but expands formative repertoires and brings students closer to the production of meaningful historical narratives. DOI: https://doi.org/10.56238/sevened2025.038-065